Konsep Natural Look dalam Tata Rias Wajah: Tinjauan Literatur pada Teknik dan Persepsi Kecantikan - Anik Maghfiroh; Dhafina Aullya; Putri Setyaningrum; Tsabita Dienalhaqqi; Maulida Kayla Talitha Ramadina; Gabriella Paska Wibowo (Garina, 2026)
The concept of the natural look in facial makeup has continued to develop along with changes in beauty trends that emphasize a simple, clean, and natural appearance. The natural look is not only understood as a makeup technique involving minimal cosmetic use, but also as a representation of modern beauty perceptions that highlight authenticity and self-confidence. This article aims to examine the concept of the natural look in facial makeup through a literature review of various relevant previous studies. The method used is a literature study by analyzing scientific journals and books discussing natural makeup techniques and beauty perceptions. The results indicate that the natural look is achieved through the use of neutral colors, light application techniques, adjustment to individual facial characteristics, and the selection of cosmetics that support a natural appearance. In addition, beauty perceptions of the natural look tend to emphasize simplicity, cleanliness, and an authentic impression. Therefore, the natural look can be understood as a combination of technical approaches in makeup and social constructions of the meaning of beauty in society.